Does Money Matter for Inflation in the Euro Area? - Sylvia Kaufmann; Peter Kugler (Oesterreichische Nationalbank (OeNB), 2005)
This paper analyses the role of M3 as an indicator for future inflation and correspondingly for current monetary policy in the euro area. We analyse the short and long run interrelationship between inflation and money growth in an error correction framework taking into account the output gap and short and long term interest rates. We find robust cointegration between money growth and inflation. In the long run, shocks in M3-growth account for 33 percent to 40 percent of the inflation forecast error variance. The effects of output gap and interest rate shocks on inflation are mainly transitory and there forecasting variance shares are negligible for medium term horizons. There is evidence for a second regime prevailing at the end of the seventies and beginning of the eighties which relates to periods of high interest rate and inflation rate levels and decreasing rates in real money growth. Overall, we present firm evidence for a stable dynamic relationship between money growth and inflation which implies that the deviation of the real money growth from its long run average is a good indicator of future inflation acceleration or deceleration. Of course, this finding provides evidence in favour of the recently de-emphasised first pillar of the ECB strategy. According to our results, however, an M3-growth rate of slightly above 5% is compatible with a non-accelerating average rate of inflation of 2%.
Keywords: 330